2017
DOI: 10.1140/epjc/s10052-017-4665-4
|View full text |Cite
|
Sign up to set email alerts
|

The lower bound violation of shear viscosity to entropy ratio due to logarithmic correction in STU model

Abstract: In this paper, we analyze the effects of thermal fluctuations on a STU black hole. We observe that these thermal fluctuations can affect the stability of a STU black hole. We will also analyze the effects of these thermal fluctuations on the thermodynamics of a STU black hole. Furthermore, in the Jacobson formalism such a modification will produce a deformation of the geometry of the STU black hole. Hence, we use the AdS/CFT correspondence to analyze the effect of such a deformation on the dual quark-gluon pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…This kind of black hole is interesting in AdS/CFT correspondence [38], for example it is possible to compute hydrodynamics and thermodynamics properties of quark-gluon plasma [39,40,41,42] in presence of quantum correction. Other properties of quark-gluon plasma like drag force [43,44,45,46], jet-quenching [47,48,49,50] and shear viscosity to entropy ratio [51] may also affected by thermal fluctuations, and this can observed by experiments [52]. It is important to note that corrections to the black hole thermodynamics can study using the non-perturbative quantum general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of black hole is interesting in AdS/CFT correspondence [38], for example it is possible to compute hydrodynamics and thermodynamics properties of quark-gluon plasma [39,40,41,42] in presence of quantum correction. Other properties of quark-gluon plasma like drag force [43,44,45,46], jet-quenching [47,48,49,50] and shear viscosity to entropy ratio [51] may also affected by thermal fluctuations, and this can observed by experiments [52]. It is important to note that corrections to the black hole thermodynamics can study using the non-perturbative quantum general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…For the future work, it is interesting to find the exponential corrected partition function of Kerr or Kerr-AdS black holes (rotating black holes [54]) and discuss the quantum effect on thermodynamics stability. Already, we used logarithmic corrected entropy [56] to study shear viscosity to entropy ratio and found the universal lower bound violated. It is interesting to consider exponential corrected entropy to study the holographic description of a quark-gluon plasma [57].…”
Section: Discussionmentioning
confidence: 99%
“…Although laboratory experiments on Quark Gluon Plasma have not shown the existence of any viscous terms, their sensitivity has not yet reached yet the quantum mechanical limit [52][53][54]. However, it is also worth noting that some models suggest the violation of such a limit under particular conditions, see for instance [55,56]. Motivated by this result in QGP, and further driven by the possibility that the early universe was filled with QGP, we shall explore viscous QGP [57][58][59] as a quantum effect in the cosmological evolution.…”
Section: Introductionmentioning
confidence: 99%

Viscous Cosmologies

Medina,
Nowakowski,
Batic
2019
Preprint